Automation and Demographic Change - Ana Lucia Abeliansky; Klaus Prettner (Global Labor Organization (GLO), 2020)
We analyze the effects of declining population growth on automation. Theoretical considerations imply that countries with lower population growth introduce automation technologies faster. We test the theoretical implication on panel data for 60 countries over the time span 1993-2013. Regression estimates support the theoretical implication, suggesting that a 1% increase in population growth is associated with an approximately 2% reduction in the growth rate of robot density. Our results are robust to the inclusion of standard control variables, different estimation methods, dynamic specifications, and changes with respect to the measurement of the stock of robots.
Keywords: J11; O33; O40; 330; Automation; Industrial Robots; Demographic Change; Declining Fertility